Firm subsidies, financial intermediation, and bank risk - Aleksandr Kazakov; Michael Koetter; Mirko Titze; Lena Tonzer (Halle Institute for Economic Research (IWH), 2022)
We study whether government subsidies can stimulate bank funding of marginal investment projects and the associated effect on financial stability. We do so by exploiting granular project-level information for the largest regional economic development programme in Germany since 1997: the Improvement of Regional Eco-nomic Structures programme (GRW). By combining the universe of subsidised firms to virtually all German local banks over the period 1998-2019, we test whether this large-scale transfer programme destabilised regional credit markets. Because GRW subsidies to firms are destabilised at the EU level, we can use it as an exogenous shock to identify bank responses. On average, firm subsidies do not affect bank lending, but reduce banks' distance to default. Average effects conflate important bank-level heterogeneity though. Conditional on various bank traits, we show that well capita-lised banks with more industry experience expand lending when being exposed to subsidised firms without exhibiting more risky financial profiles. Our results thus indicate that stable banks can act as an important facilitator of regional economic development policies. Against the backdrop of pervasive transfer payments to mitigate Covid-19 losses and in light of far-reaching transformation policies requiredto green the economy, our study bears important implications as to whether and which banks to incorporate into the design of transfer programmes.
Additional information: A completely revised version of this paper has been published as Kazakov, Aleksandr; Koetter, Michael; Titze, Mirko; Tonzer, Lena: Firm Subsidies, Financial Intermediation, and Bank Stability. IWH Discussion Papers 24/2022. Halle (Saale) 2022.
Keywords: G21; G28; H25; 330; bank stability; financial intermediation; government subsidies